Mosques as emergency shelters in disaster prone regions - Utaberta, Nangkula; Asif, Nayeem (Universiti Putra Malaysia, 2017)
Providing emergency shelter for the victims of natural disasters is part of disaster risk reduction (DRR) strategies. It is essential for the proper management of resources in the communities during emergency time. The approach toward providing emergency shelter to the victims varies in different contexts depending on the availability of suitable places. Organizations like IOM and FEMA have proposed a framework for appropriate planning and design of emergency shelters. These bodies also encourage local disaster management authorities in their guideline to utilize existing structures like schools, community centers, etc., as an emergency shelter for the victims. However, recent flood occurrence in India, UK, and Malaysia showed that the institution of the mosque is highly appropriate to be used as an emergency disaster shelter. This study analyzes the compatibility of mosque institution as a potential place for emergency shelter. The analysis follows the criteria set by IOM and FEMA to design properly functioning emergency shelter. Then, based on these criteria the design of common mosques is discussed considering different aspects such as location, capacity, and facilities. The institution of the mosque is also analyzed from the perspective of Islamic theology and how it is recommended for mosques to provide social and welfare services to the community. This paper recommends further study in this regard to proposing specific guidelines for the mosque so that it can be utilized as an existing structure for providing emergency shelter for disaster victims.